PEMANFAATAN TEKNOLOGI BIOPORI OLEH ANGGOTA HIZBUL WATHAN UNTUK MENGANTISIPASI BANJIR DAN KEKERINGAN - Umarie, Iskandar; Sanosra, Abadi (Universitas Mataram, 2024)
Hizbul Wathan in Jember Regency was reactivated along with the activation of this Scouting Movement at the national level. There are several problems in Jember Regency that GKHW can basically be a pioneer and play an important role in overcoming. These problems include the problem of drought and flooding which from year to year increases massively. The objectives of this activity are (1) GKHW members of Jember Regency are able to understand how Biopore Infiltration Holes work, (2) GKHW members of Jember Regency are skilled in making Biopore Infiltration Holes in accordance with proven standards. The steps taken in the implementation of the service program in the Muhammadiyah Association environment are strengthening the ideology of the Hizbul Wathan scouting movement, guidance and counseling on biopori technology, simulation of the application of biopori technology, making video activities and evaluating the success of the program. The implementation of this service in the Muhammadiyah Association has succeeded in improving the ability of the Scouting Movement of the Hizbul Wathan Regional Kwartir of Jember Regency from the category of less to very good. Therefore, it is expected that participants can become instructors at lower levels, namely Branch and Branch Scouts.